Un rilievo sotto sopra Modelli digitali 3D ad alta definizione sia dei fondali che delle coste - Codevintec Italiana Srl, Codevintec Italiana Srl (GEOmedia, 2009)
An upside down survey: shores and sea bed hi-res 3D digital models Laser scanning and interferometric bathymetry represent the cutting edge of coastal survey technology and can be very beneficial for mapping complicated waterside areas. The similarity of the data provided by the two systems (point cloud and intensity value) make it easy to integrate the two surveys using PolyWorks commercial software. The final product is a single 3D model made up of bathymetry and topography. Since 2004 Codevintec tested the integration of these two methodologies, carrying out a number of high resolution surveys, generating a complete and accurate digital model of areas both above and below water level, a result inimitable by any other topographical survey method. The 3D-laser scanner was an Optech ILRIS-ER that allows scanning in dynamic from the boat while a SEA SWATHplus-H wide swath sonar system was used to collect underwater topography. A combined GPS and inertial platform (Applanix POS/MV 320) is used to measure position and 3D attitude of the two sensors during the survey.